Salivary phosphate as a biomarker for human diseases - Mohammed S. Razzaque (FASEB BioAdvances, 2022)
Abstract Phosphate is a common ingredient of the daily consumed foods and is absorbed in the intestine and is excreted in the urine through the kidney to maintain the homeostatic balance. For adults, the Recommended Dietary Allowance (RDA) for phosphorus is around 700 mg/day. The change in dietary habits resulted in far more phosphate consumption (almost double) than the RDA, contributing to increased cardiovascular diseases, kidney diseases, and tumor formation. Due to a lack of clinical appreciation for the long‐term consequences of chronic phosphate burden on non‐communicable disorders, it is rapidly becoming a global health concern. The possible association between dysregulated phosphate metabolism and obesity is not studied in‐depth, mainly because such an association is believed to be nonexistent. However, in the animal model of obesity, serum phosphate level was higher than their non‐obese controls. In a similar observation line, significantly higher salivary phosphate levels were detected in obese children compared to normal‐weight children. Of clinical importance, despite the significant increase of salivary phosphate levels in obese children, the plasma phosphate levels did not change in samples collected from the same group of children. Such disparity between plasma and saliva raised the possibility that human salivary phosphate levels may be an early biomarker of childhood obesity.